KONSEP PROGRAM PENGABDIAN KEPADA MASYARAKAT PRODI AKADEMI MILITER GUNA MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Prapsetyo, Agung; Kiki Lestari (PPM Sdirjianbang Akademi Militer, 2023)
Higher Education has an obligation to implement the Tridharma of Higher Education, one of which is to organize a Community Service Program that aims to implement knowledge and creative works in the life of society, nation and state. The Military Academy as an official university also has a similar program, known as Binter (Territorial Development). This research aims to examine the concept of community service programs with territorial guidance for increasing welfare for the community. The method used is a qualitative method and is packaged with the author's experience as an educator at the Military Academy, with a literature study approach. The results of the study show that the Community Service organized by the Military Academy is a form of Territorial Development, a form of concern for the community around the Akmil Cadets training ground in order to create TNI-People unity and make the TNI professional and loved by the people.